DETERMINAN KINERJA PEGAWAI PADA BADAN KEPEGAWAIAN DAN PENGEMBANGAN SUMBER DAYA MANUSIA DAERAH KABUPATEN KERINCI: HERRY IRAWAN, SE - HERRY IRAWAN (LPPM STIA Nusantara Sakti, 2021)
Human resources (HR) is one of the most important factors that cannot be separated from an organization, both an institution or a company. The government in carrying out its duties and responsibilities are required to produce good performance. This study aims to determine the effect of organizational commitment, work environment and work discipline on employee performance. The sample used in this study were 95 respondents who were in the Kerinci Regency BKPSDMD. The analytical method used in this study is multiple linear regression analysis. The results of this study indicate that organizational commitment and significant effect on employee performance, work environment influences and significantly affects employee performance, work discipline has a significant effect on employee performance, organizational commitment, work environment and work discipline jointly influences and significantly affects employee performance Kerinci Regency BKPSDMD.